Development and industrialisation of enzymatic shrink-resist process based on modified proteases for wool machine washability - Shen, J. (2007)
There is currently considerable interest in the use of enzymes to achieve a variety of finishing effects on wool, but it is apparent that the extent of fibre degradation by enzymes is of major concern during their commercial application. Proteolytic enzymes are known to penetrate and degrade the internal wool structure during processing, causing fibre damage, rather than limiting the degradation to the cuticle cells. The ability to be able to control the exact location of proteolytic attack on wool protein structures will lead to the successful development of enzymatic treatments for achieving a variety of finishing effects for wool-containing products. This present work describes the modification of proteases so that enzymatic modification of wool fibres is restricted to the cuticle scales of the fibres. Bulk trials have demonstrated that novel modifications of the enzyme enable the reaction of the enzyme with wool to be controlled, so that less degradation of the wool occurs than in similar treatments with the native protease. An anti-felting effect has been achieved without any significant weight loss being caused by the modified protease during the treatment. This novel enzymatic process leads to environmentally friendly production of machine washable wool.